Proses Inventarisasi Aset pada Sistem Irigasi di Daerah Irigasi Rawa (DIR) Terantang - Permana, Herry Ade; wahyudi, Slamet Imam; Niam, Moh Faiqun (Universitas Islam Sultan Agung, 2025)
The inventory of irrigation infrastructure assets is a crucial step in water resource management, particularly in peatland irrigation areas with unique characteristics. However, the implementation of asset inventory in the Terantang Peatland Irrigation Area still faces various challenges, including technological limitations, human resource constraints, and discrepancies between administrative records and actual field conditions. This study aims to analyze the irrigation asset inventory process, identify challenges encountered, and formulate strategies for improving the asset recording system. A qualitative descriptive approach with a case study method was employed in the Terantang peatland irrigation area. Data were collected through field surveys, interviews with the River Basin Agency and Water User Farmer Association members, and policy document analysis. The findings indicate that asset recording is still conducted manually and is not yet integrated into a digital system, leading to delays in data updates. The main challenges in asset inventory include limited human resources, difficult area accessibility, and a lack of coordination among stakeholders. The study underscores the need for innovation in inventory methods, particularly by adopting Geographic Information System (GIS) technology and drones to enhance recording accuracy. Strengthening human resource capacity and optimizing inter-agency coordination is essential to ensure a more efficient and transparent asset recording system. The study highlights the importance of reforming irrigation asset management systems to support the sustainability of irrigation infrastructure in peatland areas.